Histological evidence of reproductive activity in lizards from the APM Manso, Chapada dos Guimarães, Mato Grosso State, Brazil - doi: 10.4025/actascibiolsci.v34i3.9228 - Adelina Ferreira; Mônica Cassel; Christine Strussmann (Acta Scientiarum: Biological Sciences, 2012)
The construction of dams causes major impacts on fauna by changing or eliminating irreversibly their habitats. The resulting changes lead to deep potential modifications on reproductive biology and population structure of lizards, snakes and amphisbaenas. The reservoir in the Multiple Use Area of Manso (APM-Manso) is located near to Chapada dos Guimarães National Park, in Mato Grosso State. We analyzed comparatively the male gonads of Anolis meridionalis, Colobosaura modesta, Cercosaura ocellata, Cnemidophorus ocellifer, Hoplocercus spinosus, Bachia bresslaui, Mabuya frenata, Micrablepharus atticolus and Tropidurus oreadicus, from APM-Manso, aiming to verify possible changes in the reproductive success according to environmental changes. Before the impoundment  A. meridionalis, Colobosaura modesta, Cercosaura ocellata, M. atticolus and T. oreadicus showed up reproductive. However, during the impoundment period they presented changes in seminiferous tubules, evidenced by the absence of spermatids and spermatozoids. B. bresslaui and M. frenata had no differences in the seminiferous tubules before and after the impoundment, being reproductive in both moments. The damming and the formation of the lake of Manso reservoir may have interfered on the reproduction of some lizards species, especially if the reproductive cycle is regulated by the rainfall of the habitat.